Multipurpose solid-state integrated circuits for sensor transfer characteristic formation - Holyaka, Roman; Hladun, Michael (Видавництво Національного університету "Львівська політехніка", 2002)
The design philosophy and elaboration results for multipurpose solid-state integrated circuits for sensor transfer characteristic formation are considered in the paper. The circuits for linearization and thermocompensation of transfer function and for multiplication of temperature coefficient are presented. Elaborated integrated circuits are characterized by simplicity and operation with low-voltage unipolar supply sources and they allow to improve precision and widen functional applications of new generation sensor devices.
Keywords: integrated circuits; transfer characteristic; signal processing; linearizator; thermocompensator